Олександру Тедєєву – 50 - Бондар, В.О. (Архіви України, 2010)
Висвітлено трудовий шлях директора Державного архіву Запорізької
області Тедєєва Олександра Сергійовича, який двадцять п’ять років присвятив
архівній справі. Освещен трудовой путь директора Государственного архива Запорожской
области Тедеева Александра Сергеевича, который двадцать пять лет своей
жизни посвятил архивному делу. This article was written on the occasion of fiftieth birthday of the director of
The State Archives of Zaporizhzhya oblast Tedeyev Olexandr Sergiovych, whose
twenty five-year seniority is connected with Zaporozhzhya Archives.